Dynamics of an SIR Epidemic Model with Information Variable and Limited Medical Resources Revisited - Caijuan Yan; Jianwen Jia; Zhen Jin (Discrete Dynamics in Nature and Society)
The stability of the SIR epidemic model with information variable and limited medical resources was studied. When the basic reproduction ratio ℛ0<1, there exists the disease-free equilibrium and when the basic reproduction ratio ℛ0>1, we obtain the sufficient conditions of the existence of the endemic equilibrium. The local asymptotical stability of equilibrium is verified by analyzing the eigenvalues and using the Routh-Hurwitz criterion. We also discuss the global asymptotical stability of the endemic equilibrium by autonomous convergence theorem. A numerical analysis is given to show the effectiveness of the main results.